Gambaran Parameter Hematologis Pada Ikan Nila (Oreochromis niloticus) Yang Diberi Vaksin DNA Streptococcus iniae Dengan Dosis Yang Berbeda - Utami, Devitha Tri; Prayitno, Slamet Budi; Hastuti, Sri; Santika, Ayi (Journal of Aquaculture Management and Technology, 2013)
Tilapia (O. niloticus) is one of freshwater species that has rapid growth and easily been cultivated. One of the constraints in cultivating Tilapia is Streptococciasis disease caused by Streptococcus iniae. The purpose of this research was to determine the haematological response of Tilapia that was given by DNA vaccine of S. iniae and challenged with S. iniae, and to determine the most effective dose of DNA vaccine based on haematological performances in the prevention of bacteria S. iniae. The fish samples used were Tilapia with length of 7,79 cm ± 0.48 as many as 150 animals or 10 animals per treatment. Five (5) treatments and three (3) replications were administered in this research, there were A (0 ŋg/µL), B (10ŋg/µL), C (20ŋg/µL), D (30ŋg/µL), dan E (40ŋg/µL) of DNA vaccines the injected intramuscularly. Fish were maintained for 30 days, then challenged with S. iniae for 14 days. Measurement of haematological performances include haematocrit, total leukocyte, differential leukocytes, and phagocytosis index carried out every 7 days. The observation of clinical signs of fish after challenge by S. iniae obtained that fish in A and B treatment showed clinical signs more quickly than fish in C, D, and E treatment. The results showed that DNA vaccines S. iniae in E treatment significantly different on haematocrit levels (25,67%), total leukocytes (9,46x104 cells/mm3), lymphocytes (80,33%), monocytes (5,67%), neutrophils (14%), phagocytosis index (22,33%), and survival rate (70%). It can be conclude that dosage of DNA vaccine 40ng/μl is the most effective dosage which is immunogenic and protective in raising Tilapia immunity against bacterial S. iniae based on haematological aspects.